Influence of La2O3, Pr2O3 and CeO2 on the nonlinear properties of SnO2 multicomponent varistors - Oliveira, M. M.; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
The influence of La2O3, Pr2O3 and CeO2 on a new class of polycrystalline ceramics with nonlinear properties based on SnO2, was investigated. La2O3 and Pr2O3 were found to precipitate at the grain boundary region, causing a considerable increase in the nonlinear behavior. It was found that CeO2 forms a solid solution in the bulk but. unlike La2O3 and Pr2O3, it does not increase the nonlinear behavior. A higher nonlinear coefficient of similar to80 was obtained for La2O3-doped SnO2-based systems. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: tin oxide; nonlinear properties; varistors